Design and implementation of modified multilevel sepic converter for PV based apllications - Arunkumari T; I. Jagadeesh; Indragandhi V (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
In this manuscript, a DC-DC converter of modified multilevel sepic model with single switch is proposed here. The designed converter combines the voltage tripler circuit, which improves the voltage gain and reduces the voltage ripple of the system. Another feature of the designed converter is reduces the voltage stress and utilized for PV based applications. The operation of the designed converter in Continuous-Conduction Mode (CCM) is discussed. The converter boosts the PV input voltage of 30 V to 400 V output voltages. The efficiency attained by the designed converter is 94%. The Theoretical analysis of the designed converter is presented and it is done with MATLAB simulink. To analyse the performance of this DC-DC converter a model was developed and tested.  From the experimental results obtained, it is analysed that the converter performs better and suitable for PV based application.